2021
DOI: 10.3390/catal11010108
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics Study of the Hydrodeoxygenation of Xylitol over a ReOx-Pd/CeO2 Catalyst

Abstract: In this study, we elucidate the reaction kinetics for the simultaneous hydrodeoxygenation of xylitol to 1,2-dideoxypentitol and 1,2,5-pentanetriol over a ReOx-Pd/CeO2 (2.0 weight% Re, 0.30 weight% Pd) catalyst. The reaction was determined to be a zero-order reaction with respect to xylitol. The activation energy was elucidated through an Arrhenius relationship as well as non-Arrhenius kinetics. The Arrhenius relationship was investigated at 150–170 °C and a constant H2 pressure of 10 bar resulting in an activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…147 In contrast, ReO x -Pd/CeO 2 catalysts, in which Pd species have the same role as Au and Ag to reduce Re, gave the saturated products through the high hydrogenation activity of Pd. [151][152][153][154] This reaction system is called "DODH + hydrogenation", and the reaction scheme is shown in Fig. 13.…”
Section: Double-hydrodeoxygenation Of Alkyl Glycosides With Cis-vicin...mentioning
confidence: 99%
“…147 In contrast, ReO x -Pd/CeO 2 catalysts, in which Pd species have the same role as Au and Ag to reduce Re, gave the saturated products through the high hydrogenation activity of Pd. [151][152][153][154] This reaction system is called "DODH + hydrogenation", and the reaction scheme is shown in Fig. 13.…”
Section: Double-hydrodeoxygenation Of Alkyl Glycosides With Cis-vicin...mentioning
confidence: 99%
“…Due to the selectivity of rhenium‐based catalysts towards the hydrogenolysis of C−O bonds rather than C−C bonds, bimetallic catalysts of general composition M−ReO x (M=noble metal) have been studied for the hydrogenolysis of bio‐derived polyols such as glycerol [66] . Silica‐supported Rh−ReO x , Ru−ReO x , Pt−ReO x , Ir−ReO x and Pd−ReO x were evaluated in this reaction by Amada et al., [67] where Rh−ReO x was the most active, yet Ir−ReO x had the highest selectivity to the desired product 1,3‐propanediol ‐ interestingly, Pd−ReO x /SiO 2 showed no activity in the hydrogenolysis of glycerol, [67] whereas Pd−ReO x /CeO 2 is reported as active in the hydrodeoxygenation of other polyols, [68,69] indicating an influence of the CeO 2 support [70] . Rh−ReO x was among the first bimetallic catalyst containing ReO x studied by the research group of Tomishige et al.…”
Section: Hydrogenation Of Platform Moleculesmentioning
confidence: 99%
“…Various heterogeneous catalysts have been reported for the simultaneous HDO of polyols and cyclic ethers. The catalysts are comprised of supported oxophilic metals (e.g., ReO x, WO x ) promoted by noble metals (e.g., Ir, Pd, Rh). , Recently, studies have demonstrated the removal of hydroxyls from erythritol over Ir-ReO x /SiO 2 , Ir-ReO x /TiO 2 , Pt-WO x /SiO 2 , and ReO x -Pd/CeO 2 , mainly producing monomer building blocks, such as 1,2-BDO, 1,4-BDO, and 1,3-butanediol (1,3-BDO). ,,,, Furthermore, the single-step transformation of vicinal hydroxyls in 1,4-AHERY to the corresponding alkene (2,5-dihydrofuran (2,5-DHF)) by DODH has been demonstrated over supported ReO x . Researchers have also demonstrate that the addition of Pd to ReO x supported on CeO 2 leads to conversion of 1,4-AHERY to tetrahydrofuran (THF) at 413 K and a hydrogen pressure of 80 bar with 99% selectivity at 38% conversion by simultaneous HDO. , On the basis of kinetic and computational studies, the active sites proposed for the ReO x -Pd/CeO 2 were isolated Re 4+ species formed by the reduction of Re 6+ species in the presence of Pd-dissociated hydrogen atoms. , There has been spectroscopic evidence that the ReO x exists in a mono-oxo (ReO) and a dioxo (OReO) state on the ReO x -Pd/CeO 2 catalyst, which further supports the proposed active sites .…”
Section: Introductionmentioning
confidence: 99%